2022
DOI: 10.3389/fphar.2021.750173
|View full text |Cite
|
Sign up to set email alerts
|

Intravenous Immunoglobulin Combined With Corticosteroids for the Treatment of Stevens–Johnson Syndrome/Toxic Epidermal Necrolysis: A Propensity-Matched Retrospective Study in China

Abstract: Background: Stevens–Johnson syndrome (SJS) and toxic epidermal necrolysis (TEN) are rare but life-threatening severe adverse drug reactions. The use of corticosteroids and intravenous immunoglobulin (IVIg) in SJS/TEN remains controversial.Methods: In this single-center, observational, propensity-matched, retrospective study, we collected a total of 224 patients with SJS/TEN who were hospitalized in our department from 2008 to 2019; according to treatment with IVIg combined with corticosteroids or with corticos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 61 publications
0
2
0
Order By: Relevance
“…Fluocinonide 0.05 % cream was administered intravaginally for vaginal involvement. The impact of IVIG on recovery time and mortality has been studied [16,17]. A Meta-analysis showed that IVIG combined with corticosteroid could reduce recovery time for SJS and TEN whereas, its impact on reducing mortality is not significant [16].…”
Section: Discussionmentioning
confidence: 99%
“…Fluocinonide 0.05 % cream was administered intravaginally for vaginal involvement. The impact of IVIG on recovery time and mortality has been studied [16,17]. A Meta-analysis showed that IVIG combined with corticosteroid could reduce recovery time for SJS and TEN whereas, its impact on reducing mortality is not significant [16].…”
Section: Discussionmentioning
confidence: 99%
“…After it was discovered that pooled person intravenous immunoglobulins (IVIG) have anti-Fas capability in vitro, IVIG were examined for the therapy of TEN, and their effects were documented in a variety of uncontrolled investigations [69]. The antimicrobial efficacy of IVIG in TEN has been examined in several published studies and 12 uncontrolled clinical studies with 10 patients or more to date.…”
Section: Drug Therapymentioning
confidence: 99%